"Excessive muscle strain as the direct cause of injury" should not be generalized to hamstring muscle strain injury in sprinting - Ruan, M. F. (Journal of Sport and Health Science, 2018)
The debate about the mechanisms of hamstring injuries in sprinting in the Journal of Sport and Health Science reminds of the discussion of the force enhancement mechanisms in stretch-shortening cycles (SSCs) 20 years ago in the Journal of Applied Biomechanics. The controversies concerning the proposed mechanisms were mainly due to the difference in the levels of observation between animal and human studies.An important question debated 20 years ago was "Are the muscle fibers and muscle spindles lengthened during SSCs?" a question that is also important to the current discussion on hamstring strain injuries.